Stability and seepage analyses of residual soil slope from old alluvium in Singapore - Ng, Qi Long (Nanyang Technological University, 2020)
The world is reeling from the effects of climate change as evident from high intensity rainfalls occurring on an unprecedented scale. Past research has shown that these changes in rainfall pattern play a primary role in causing slope failure. Rainfall-resulted slope failures can be disruptive in a densely populated environment like Singapore and is thus imperative to study the stability of existing slopes in response to higher rainfall intensities expected in the future. Therefore, this study aims to evaluate the stability of residual soil slope overlying the Old Alluvium (OA) at Bidadari. The scope of the project involved various laboratory measurements of residual soil samples from Bidadari, followed by two-dimensional seepage and stability analyses of the slope. The analyses are required to investigate the changes in factor of safety (FoS) based on extreme and current rainfall intensities in Singapore. The laboratory test results showed that the residual soil stratum from the surface down to 5m has a bimodal SWCC while soil at deeper depths has a unimodal SWCC. The percentage of fines from the surface down to 5m depth is lower in comparison to deeper depths, which results in a low air-entry value. The saturated permeability of soil nearer to the surface is shown to be higher and was reflected in rapid changes in water content during numerical simulations and readings registered from field instrumentation. The effective cohesion and effective friction angle of the on-site residual soil were found to be 11kPa and 34o, respectively. The results showed the FoS of the Bidadari slope is well above the limit of 1.5 imposed by BCA. The numerical model was verified with field instrumentation readings and was shown to adequately reflect on-site conditions.